Impact of combined at-home bleaching and whitening toothpaste use on the surface and color of a composite resin - Carolina Meneghin Barbosa; Renata Siqueira Scatolin; Waldemir Francisco Vieira-Junior; Marcia Hiromi Tanaka; Laura Nobre Ferraz (Restorative Dentistry & Endodontics, 2023)
ObjectiveThis in vitro study aimed to evaluate the effects of different whitening toothpastes on a composite resin during at-home bleaching with 10% carbamide peroxide.Materials and MethodsSixty samples (7 mm × 2 mm) were used for color and roughness analyses, while another 60 samples (3 mm × 2 mm) were utilized to assess microhardness. The factors analyzed included toothpaste, for which 5 options with varying active agents were tested (distilled water; conventional toothpaste; whitening toothpaste with abrasive agents; whitening toothpaste with abrasive and chemical agents; and whitening toothpaste with abrasive, chemical, and bleaching agents). Brushing and application of whitening gel were performed for 14 days. Surface microhardness (SMH), surface roughness (Ra), and color (∆L*, ∆a*, ∆b, ∆E*ab, and ∆E00) were analyzed. The Ra and SMH data were analyzed using mixed generalized linear models for repeated measures, while the color results were assessed using the Kruskal-Wallis and Dunn tests.ResultsBetween the initial and final time points, all groups demonstrated significant increases in Ra and reductions in SMH. No significant differences were found between groups for SMH at the final time point, at which all groups differed from the distilled water group. Conventional toothpaste exhibited the lowest Ra, while whitening toothpaste with abrasive agent had the highest value. No significant differences were observed in ∆L*, ∆a*, and ∆b.ConclusionsWhile toothpaste composition did not affect the color stability and microhardness of resin composite, combining toothbrushing with whitening toothpaste and at-home bleaching enhanced the change in Ra.